2019
DOI: 10.1590/1413-81232018247.18752017
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver’s oral health literacy is associated with prevalence of untreated dental caries in preschool children

Abstract: The aim of this study was to evaluate the relationship between oral health literacy (OHL) among caregivers and untreated dental caries among preschoolers. A cross-sectional study was conducted involving 415 preschool children and their caregivers from Curitiba, Brazil. The children were examined for dental caries and dental plaque. The caregivers’ OHL was evaluated using an instrument translated and validated for Brazilian Portuguese: the Brazilian Rapid Estimate of Adult Literacy in Dentistry-30. The prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 23 publications
2
34
0
9
Order By: Relevance
“…After exclusion of duplicates, 1,084 investigations were screened based on title/abstract and sixty‐nine of those had their full text retrieved for analysis. Eleven studies were included in the present systematic review: nine cross‐sectional and two cohort studies (Table ). Most full‐texts were excluded due to not concerning OHL, for reporting unrelated outcomes and for not addressing outcomes in children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After exclusion of duplicates, 1,084 investigations were screened based on title/abstract and sixty‐nine of those had their full text retrieved for analysis. Eleven studies were included in the present systematic review: nine cross‐sectional and two cohort studies (Table ). Most full‐texts were excluded due to not concerning OHL, for reporting unrelated outcomes and for not addressing outcomes in children.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies ( n = 8) were set in the United States, whereas one investigation took place in China, one in Brazil and the other in Iran.…”
Section: Resultsmentioning
confidence: 99%
“…Accepting that children's oral health is influenced by family characteristics, it is suggested that parental OHL level is a key family factor in this context. Previous studies have identified that children whose parents have low OHL levels have a higher prevalence of dental caries, increased dental plaque levels, and were more like to not have visited a dentist in the previous year …”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies investigating the relationship between parental OHL and child oral health have relied on word‐recognition instruments . Currently, there are three instruments to evaluate OHL validated in the Brazilian Portuguese language.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation